Identification of Scientific Knowledge of the Patehan Tradition of Yogyakarta Palace as a Source of Natural Science Learning - Larassati, Annasya Sakha Alika; Suciati*, Suciati; Sari, Meida Wulan; Silvita, Silvita; Prasetyo, Opik; Rachman, Hening Triandika (Universitas Syiah Kuala, 2025)
The integration of local wisdom into science learning faces challenges due to the focus on theoretical understanding rather than real-world applications. Teachers often overlook the potential of local wisdom in science education, and the process of incorporating cultural phenomena as scientific learning topics is perceived as complex. This study aims to identify the scientific knowledge embedded in the